2019
DOI: 10.1111/camh.12331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mentoring on socio‐emotional and mental health outcomes of youth with learning disabilities and attention‐deficit hyperactivity disorder

Abstract: Background Learning disabilities (LD) and attention‐deficit hyperactivity disorder (ADHD) are often accompanied by significant socio‐emotional impairments and mental health challenges. However, there is a lack of controlled, quantitative research on potential interventions to address this issue. The current study evaluated the impact of a near‐peer mentoring program for youth with LD/ADHD designed to promote socio‐emotional well‐being. Methods Youth with LD/ADHD who participated in the mentoring program (Mento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 60 publications
(81 reference statements)
1
17
0
Order By: Relevance
“…The findings of this study resonate with previous research findings which have found significant relationships between disability and poor socio-emotional health (see Bakopoulou and Dockrell 2016;Bryan et al 2004;Davis and Watson 2001; A. Swift et al et al 2019;Haft et al 2019;Lindsay 2007;Van Agt et al 2011) as disabled children were found to be up to 16.3 times more likely to experience poor socio-emotional outcomes over time than their peers without disability. This study found no significant interaction between migrant background and disability and poor socio-emotional outcomes, which is in line with previous findings (Cotter et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study resonate with previous research findings which have found significant relationships between disability and poor socio-emotional health (see Bakopoulou and Dockrell 2016;Bryan et al 2004;Davis and Watson 2001; A. Swift et al et al 2019;Haft et al 2019;Lindsay 2007;Van Agt et al 2011) as disabled children were found to be up to 16.3 times more likely to experience poor socio-emotional outcomes over time than their peers without disability. This study found no significant interaction between migrant background and disability and poor socio-emotional outcomes, which is in line with previous findings (Cotter et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, mentorship programs specifically have been found to affect participating adolescents’ depression [ 8 , 9 , 22 ]. In a school-based mentorship program that paired U.S. elementary and middle school students with learning disabilities and/or attention-deficit hyperactivity disorder [ADHD] with mentors (high school and college students who also had learning disabilities and/or ADHD) showed that participating students had decreased depression after participation in the program compared to baseline, while students in the control group experienced increases in depression over the period of the mentorship program [ 8 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have found that one contributing factor for high levels of adolescent depression is neglect by parents or caregivers [ 4 , 5 , 6 , 7 ]. One intervention that has been found to be successful in reducing levels of depression among high-risk adolescents are formal mentorship programs, or programs where one person (the mentee) is matched with another person (the mentor) who provides support in various ways (e.g., [ 8 , 9 ]). Formal mentorship programs are distinguished from informal mentorship programs by the fact that formal programs have a set of guidelines or a process in which the mentorship takes place, while informal mentoring is more unstructured [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some comorbidities arise from the stress and frustration that emerge as patients acknowledge their behavioral differences and struggle to conform to a social setting in order to avoid social repercussions or academic consequences for their outbursts [ 31 ]. For example, difficulty with social skills can lead to higher risks for disorders such as anxiety or depression [ 32 ]. Children with ADHD can suffer from a certain degree of emotional impairment, with difficulty controlling feelings including anger or aggression [ 29 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%